2000
DOI: 10.1159/000055635
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid Hormone Signaling Regulates the ‘Epithelial Sodium Channel’ in Fibroblasts from Human Cornea

Abstract: We investigated the regulation of sodium absorption by steroid hormones in embryologically diverse cells from the human eye. A cell extract from human corneal fibroblasts was positive for both the epithelial sodium channel (ENaC) and the mineralocorticoid receptor (MCR) as 82- to 85-kD and 102-kD bands, respectively, by the Western blot technique. In fluorescent, confocal and electron microscopy, the MCR was revealed as a nucleocytoplasmic protein, whereas the ENaC was almost exclusively membrane bound; both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…55 This conclusion is further supported by molecular evidence of ENaC expression in corneal epithelial cells. [32][33][34]36,56 ENaC expression has also been reported in rabbit and human conjunctival tissue. 30 Interestingly, in the latter study, topical application of amiloride was shown to increase the quantity of The present study shows ␣-, ␤-, and ␥-, but not ␦-, ENaC mRNA expression in the human cornea.…”
Section: Epithelial ␣␤␥ Configuration Of Enac In Corneal Endothelial mentioning
confidence: 99%
See 2 more Smart Citations
“…55 This conclusion is further supported by molecular evidence of ENaC expression in corneal epithelial cells. [32][33][34]36,56 ENaC expression has also been reported in rabbit and human conjunctival tissue. 30 Interestingly, in the latter study, topical application of amiloride was shown to increase the quantity of The present study shows ␣-, ␤-, and ␥-, but not ␦-, ENaC mRNA expression in the human cornea.…”
Section: Epithelial ␣␤␥ Configuration Of Enac In Corneal Endothelial mentioning
confidence: 99%
“…12,29,33,63,67 ENaC has been detected in Müller glial cells 12,28,37 and RPE, 29 in which the mineralocorticoid receptor may colocalize with ENaC. Moreover, aldosterone has been shown to upregulate ENaC expression in Müller glial cells 12 and in the RPE.…”
Section: Enac and Retinal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found (Kuang et al,'93) that the most efficient inhibitor of this entry is phenamil, a compound that is specific for an epithelial-type Na þ channel (ENaC). The presence in rat (Mirshahi et al,'99) and human (Mirshahi et al, 2001) corneal endothelium has been established by immunocytochemistry. Preliminary immunocytochemical work in our laboratory is consistent with an apical location for EnaC.…”
Section: Sodium Entry Routesmentioning
confidence: 99%
“…The presence of MR and HSD2 in the trabecular meshwork is described controversially [22–24]. Mineralocorticoid effects are thought to be mediated by epithelial sodium channels (EnaC) [38, 39], which are also present at numerous places in the anterior eye segment [4043]. These channels might serve two different functions: one is fluid secretion from the ciliary epithelium (increase of aqueous humour formation), and the other is regulation of the trabecular meshwork resistance by volume regulation of the trabecular meshwork cells.…”
Section: Mineralocorticoids Have Some Effects In the Eyementioning
confidence: 99%